Ultrasound Analysis of Respiration-Related Muscles in Rats - Zhan, Shubei; Zheng, Bin; Li, Mengyi; Xu, Lin; Chen, Chengchun; Huang, Peizhen (Frontiers in Genetics, 2022)
The purpose of this study is to evaluate the effectiveness of ultrasound technology in analyzing respiratory-related muscles in rats. Methods: The respiratory parameters were measured by ultrasound, including: diaphragm end-expiratory thickness, average rectus abdominis (RA) thickness and RA area, and compared with histological results. Spearman's correlation and logistic regression analysis were used to detect the difference between ultrasound results and the correlation of histological examination, Student t test was performed to compare the difference between ultrasound results and histological examination data. Results: The end-expiratory thickness of the right diaphragm (0.76 ± 0.05 VS. 0.82 ± 0.04 mm), the end-expiratory thickness of the left diaphragm (0.79 ± 0.08 VS. 0.85 ± 0.07 mm), and the average thickness of the right RA ( 1.69 ± 0.18 VS. 2.17 ± 0.32 mm), left RA average thickness (1.74 ± 0.15VS. 2.08 ± 0.27 mm), right RA area (22.8 ± 1.52 VS. 21.9 ± 1.18 mm2), left RA area (23.4 ± 1.43 VS. 21.8 ± 0.96 mm2)，there is no significant difference between ultrasound and histological values ( p>0.05), and there is a significant positive correlation between ultrasound and histological values (p<0.05); in addition, tidal volume is significantly positively correlated with the total area of RA (r = 0.812, p = 0.001), rapid shallow breathing index (RSBI) is significantly negatively correlated with the total area of RA (r = -0.618, p = 0.017), and the average diaphragm Muscle TF was significantly positively correlated with tidal volume (r = 0.603, p = 0.021). Conclusion: Ultrasound imaging is highly accurate and reproducible, and can be used to evaluate the structure and function of the diaphragm and RA in rats.